Musical theatre in translation: A semiotic analysis of Jacques Brel's "L'Homme de la Mancha" - Hubsch, Jean-Frederic (University of Ottawa (Canada), 2006)
Translation of musical theatre has been afforded little academic study. This project aims to help fill this gap in order to develop the study of musical theatre in translation studies. This begins with defining the specificity of musical theatre as a form, using prior work in both the study and translation of theatre and of opera. The goal is to position musical theatre as an object for analysis and to outline the constraints attached to the translation thereof. An analysis of the effect on translation of some of these constraints follows based on notions from discourse analysis and music interpretation. Finally, this semiotic framework focussing on the use of isotopy is applied to a specific case of musical theatre translation, that of Man of La Mancha translated into French by Jacques Brel as L'homme de La Mancha.
Keywords: Literature, Romance.; Music.; Theater.; Literature, American.; Language, General.